Optimization-Based String Method for Finding Minimum Energy Path (Communications in Computational Physics, 2014)
We present an efficient algorithm for calculating the minimum energy path(MEP) and energy barriers between local minima on a multidimensional potential energy surface (PES). Such paths play a central role in the understanding of transitionpathways between metastable states. Our method relies on the original formulation ofthe string method [Phys. Rev. B, 66, 052301 (2002)], i.e. to evolve a smooth curve alonga direction normal to the curve. The algorithm works by performing minimizationsteps on hyperplanes normal to the curve. Therefore the problem of finding MEP onthe PES is remodeled as a set of constrained minimization problems. This provides theflexibility of using minimization algorithms faster than the steepest descent methodused in the simplified string method [J. Chem. Phys., 126(16), 164103 (2007)]. At thesame time, it provides a more direct analog of the finite temperature string method.The applicability of the algorithm is demonstrated using various examples.